Can we build theories of understanding on the basis of mirror neurons? - Pacholik-Żuromska, Anita (Hybris, 2015)
The discovery of mirror neurons and the characterization of their response properties is certainly an important achievement in neurophysiology and cognitive neuroscience. The reference to the role of mirror neurons in ‘reading’ the intentions of other creatures and in the learning process fulfils an explanatory function in understanding many cognitive phenomena beginning from imitating, towards understanding, and finishing with complex social interactions. The focus of this paper is to review selected approaches to the role of mirror neurons in mental activity as understanding, and to conclude with some possible implications for researches on mirror neurons for philosophical theories of understanding.